1986
DOI: 10.1073/pnas.83.11.3934
|View full text |Cite
|
Sign up to set email alerts
|

Actively transcribed genes in the raf oncogene group, located on the X chromosome in mouse and human.

Abstract: Murine and human cDNAs, related to but distinct from c-raf-1, have been isolated and designated mA-raf and hA-raf, respectively. The mA-raf and hA-raf cDNAs detect the same murine and human fragments in Southern blots of restriction enzyme-cleaved murine and human cellular DNA. The murine restriction enzyme fragments homologous to mA-raf cDNA cosegregate with mouse chromosome X in a panel of Chinese hamster-mouse hybrid cells, thus localizing the mA-raf locus to mouse chromosome X. Two independently segregatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…RG7204 may also be effective in treating cancers other than melanoma, as shown by its antiproliferative activity in colorectal cancer and other tumor cell lines with the BRAF V600E mutation and by its RG7204 antitumor activity in BRAF V600E -bearing colorectal cancer xenograft models. 6 However, it seems that the specific molecular effect of RG7204 may differ in different cell types. A previous study in a thyroid cancer cell line showed inhibition of cell growth but very little induction of apoptosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…RG7204 may also be effective in treating cancers other than melanoma, as shown by its antiproliferative activity in colorectal cancer and other tumor cell lines with the BRAF V600E mutation and by its RG7204 antitumor activity in BRAF V600E -bearing colorectal cancer xenograft models. 6 However, it seems that the specific molecular effect of RG7204 may differ in different cell types. A previous study in a thyroid cancer cell line showed inhibition of cell growth but very little induction of apoptosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…27 Our finding that constitutive MAP kinase activity in v-raf transformed cells quickly led to the identification of the mitogen-activated kinase kinase MEK as first physiological Raf substrate, thereby completing the description of the classical mitogenic cascade. [28][29][30] Subsequently, the paralogues A-Raf [31][32][33] and B-Raf 34,35 were identified. Although all 3 Raf isoforms share considerable sequence similarity, 36 they exhibit beneath common also individual functions, which are still far from being fully understood.…”
mentioning
confidence: 99%
“…Around the same time, chicken Raf was cloned from an avian virus (Mill-Hill No 2) and termed v-mil (Jansen et al, 1983(Jansen et al, , 1984. Cloning of human CRAF, ARAF and BRAF followed shortly afterwards (Bonner et al, 1985;Huebner et al, 1986;Beck et al, 1987;Ikawa et al, 1988;reviewed in Wellbrock et al, 2004). In 2003, an omission of three nucleotides from the first exon in the sequence of the human BRAF gene in NCBI was identified and corrected, resulting in the change of the numbering of protein residues (Kumar et al, 2003a).…”
mentioning
confidence: 99%